Bacteriological Quality of Street Vended Ready to Eat Legume and Vegetable Based Foods in Bahir Dar, Amhara Regional State, North Western Ethiopia - Tesfaye, Mohammed (International Journal For Research In Agricultural And Food Science, 2019)
Street vending foods are readily available sources of meals for many people butthe micro- biological quality of such food is always in doubt. This is due to widespread food borne diseases and the increment of wayside food vendors who lack an adequate understanding of the basic food safety issues. The aim of this study was to determine the microbial quality of legume and vegetable based foods and the hygienic practices of street venders who sold legume and vegetable based foods in Bahir Dar town from December 2013 to June 2014. Sixty food samples were collected from different locations Aerobic mesophilic, total coliforms, fecal coliforms and Staphylococcus aureus counts were determined using standard methods. Out of the total samples, 28.3%,33.3%,18.3% and 51.7% of the foods were above acceptable limit for aerobic mesophilic count, S. aureus, total coliforms and thermotolerant, respectively. While S.aureus and thermotolerant coliforms were not detected in 1(21.7%) and 29(48.3%) of the food samples, respectively. Only 7(11.7%) of the total sample was hazardous due to high mean count of S. aureus. There was no statistically significance differences in bacterial counts between legume and vegetable based food (p>0.05). On the other hands, most of the water samples used to wash ready to eat foods and utensils in food preparation were contaminated and fell above WHO drinking water standards and are therefore doubtful quality. In addition, observational checklist shows majority of the handlers did not practice hand washing during food preparation and without reheating to serve prepared foods. Most of the ready-to-eat foods had acceptable levels of contamination; however can posing potential risks to consumers and it requires the local authority emphasize on educating the ready-to-eat food handlers on food and personal hygiene to ensure the hygienic standards and food safety.